Parenteral nutrition - the nurse’s role on patient care - Rutkowska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Prenatal nutrition is a great medical achievement in the 20th century. In Poland, the interest of the method grew during the 1980s of the past century. For beneficial prenatal nutrition there have been necessity of wide knowledge of the therapeutic team. One of the team’s member is a nurse. Consequently, the effects of the prenatal nutrition depend on the nurse’s skills and knowledge.